Unreal cities and valleys of ashes in post-Great War European and American society: a comparative examination of T. S. Eliot’s The Waste Land and F. Scott Fitzgerald’s The Great Gatsby - Wessels, J.A. (Andries) (University of Pretoria, 2024)
Dissertation (MA (English))--University of Pretoria, 2019.